Public Perception as a Mediator between Blue Ocean Strategy-Based Environmental CSR and Community Participation in Rinjani Indah Eco-Village, Bogor - Nunung Nurzananh; Besar Agung Martono (Yayasan Amerta Insan Unggul, 2024)
Innovative Corporate Social Responsibility (CSR) based on Blue Ocean Strategy is key to enhancing community participation in environmental programs. This study analyzes the influence of program innovation, value differentiation, and resource efficiency on community perception and participation in the Environmental Friendly Village (KRL) Rinjani Indah, Gunung Putri, Bogor. A quantitative method with purposive sampling and Structural Equation Modeling (SEM) analysis using SmartPLS 3.0 was applied to 90 respondents. The results show that program innovation, value differentiation, and resource efficiency have a significant positive effect on community perception and participation. Community perception also plays a significant mediating role between program innovation and value differentiation on community participation, while resource efficiency is not effective through community perception. These findings provide important contributions for developing more effective and sustainable CSR programs. Future research is recommended to expand variables and methods to enrich the results.